RESEARCH TREND OF CULTURAL VILLAGE AS A COMMUNITY-BASED TOURISM: A SYSTEMATIC LITERATURE 2000-2020 - Sulistiono, Bagus (Universitas Diponegoro, 2024)
This study aims to collect, review, synthesize, and analyze a collection of scientific articles that focus on discussing the outcomes or results of a form of community-based tourism (CBT) practices worldwide. The specific form of CBT examined in this study is the Cultural Village and similar village-based initiatives. The research period spans over 20 years, from 2000 to 2020. In addition to examining the evolution of research trends and mapping the literature on these topics, this study proposes a framework for assessing the outcomes of this form of community-based tourism. The Systematic Literature Review (SLR) was employed to collect and analyze relevant scientific articles. The SLR method involves at least six main stages. Ten scientific literature databases served as sources of information for retrieving related articles. A total of 61 articles were selected during the search and filtering process. The primary findings indicate that properly managed Cultural Villages can positively impact three main aspects: the economy, the environment, and the socio-culture. This phenomenon is termed the